Application of the gastrointestinal decompression device in home-based continuing care of patients with pressure injury (胃肠减压器在压力性损伤患者居家延续护理中的应用) - CHEN Zhuo (陈卓); LIU Na (刘娜); YOU Xin (尤欣); SUN Hongyan (孙红艳); LI Dan (李丹); ZHAO Chunhua (赵春华) (中西医结合护理)
The aim of this paper is to evaluate the application of gastrointestinal decompression device instead of Vacuum Sealing Drainage (VSD) in the home-based nursing of patients with pressure injury. Totally 30 patients with stage Ⅲ or above pressure injury who received treatment using the gastrointestinal decompression device instead of VSD were selected as the research objects. A home-based nursing plan was carried out to enhance the observation and maintenance of decompression device, drainage liquid and tube. The use of disposable gastrointestinal decompression device instead of VSD can be more convenient in the treatment of stage Ⅲ and above pressure injury. The use of disposable gastrointestinal decompression device is potentially effective to improve wound healing and reduce the nursing operation and economic burden of family members. (本文探讨胃肠减压器在压力性损伤患者居家护理中的应用效果。选取30例Ⅲ期及以上压力性损伤患者为研究对象, 均不具备负压封闭引流条件。医护人员使用一次性胃肠减压器代替负压封闭引流, 在居家换药护理过程中加强封闭持续负压装置、引流液和管路的观察护理。一次性胃肠减压器代替负压封闭引流技术引流治疗Ⅲ期及以上压力性损伤有效, 能够促进伤口愈合, 减轻家属的护理操作及经济负担。)